Étude nivométrique sur le bassin de la rivière Sainte-Anne de Beaupré - Héroux, Valbert; Grenier, André (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1961)
During the winter 1959-60, the authors have studied various characteristics of the snow cover in the basin of the river Ste. Anne de Beaupré. They observed that the density of snow always varied between 2.0 and 2.5. The classical method of converting 10 inches of snow to one inch of water then appears a debatable question. The graphs of snow precipitations established over a period of ten years suggest that the basin of the Ste. Anne de Beaupré is typical of a regime with two maximums which occur sometimes between December and March.